Darunnajah Vote System Application Design Using PHP Programming Language - Panggabean, Supriadi; Wahyu Joko Saputro; Faishal Wafiq Zakiy; Tutik Lestari; Ahmad Rifqi (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2023)
Voting is the most important part of choosing leaders in an organization or institution, especially for those of us who use a democratic system. The election of organizational leaders in Darunnajah is still carried out conventionally, elections still use paper to select organizational leaders which is carried out by recording and counting the name or picture of one of the candidates. Creating the Darunnajah Vote System in the form of a web application for the election of organizational leaders in the Darunnajah environment can speed up the voting process. The web application is built using PHP and MySQL with features of user management, class management, candidate management, and E-Voting. This study aims to build an e-voting system that is expected to provide voting results quickly, and accurately and can be monitored in real-time during the implementation of the leader election. This system development method uses a web application-based SDLC Waterfall model. Testing using the black box method, every feature contained in the Darunnajah Vote System application, namely the Admin Login feature, User Login, User Voting, and User Data Processing features runs normally and functions properly.